2019
DOI: 10.1101/572933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Cytoplasmic Viscosity on Red Blood Cell Migration in Small Arteriole-level Confinements

Abstract: The dynamics of red blood cells in small arterioles are important as these dynamics affect many physiological processes such as hemostasis and thrombosis. However, studying red blood cell flows theoretically is challenging due to the complex shapes of red blood cells and the non-trivial viscosity contrast of a red blood cell. To date little progress has been made studying small arteriole flows (20-40µm) with a hematocrit (red blood cell volume fraction) of 10-20% and a physiological viscosity contrast. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Although hardened RBCs are not expected to be fully rigid at the concentration of GA used, membrane stiffening affects both individual RBC motion and collision dynamics in RBC suspensions; these effects might combine with the altered local shear gradients in the measured flows to give rise to the observed concentration profiles. 25,34 Wall induced lift forces are expected to be "screened" in the case of dense RBC suspensions 25 which might explain the absence of any observed changes in hematocrit distribution for dense RBC suspensions with a change in viscosity contrast between cells and the suspending medium (hence RBC deformability) reported in the recent numerical studies by de Haan et al 48 and Saadat et al 49 However, the increased tumbling motion of the hardened cells is thought to enhance the collision rate between RBCs and the wall producing larger displacements and…”
Section: Discussionmentioning
confidence: 97%
“…Although hardened RBCs are not expected to be fully rigid at the concentration of GA used, membrane stiffening affects both individual RBC motion and collision dynamics in RBC suspensions; these effects might combine with the altered local shear gradients in the measured flows to give rise to the observed concentration profiles. 25,34 Wall induced lift forces are expected to be "screened" in the case of dense RBC suspensions 25 which might explain the absence of any observed changes in hematocrit distribution for dense RBC suspensions with a change in viscosity contrast between cells and the suspending medium (hence RBC deformability) reported in the recent numerical studies by de Haan et al 48 and Saadat et al 49 However, the increased tumbling motion of the hardened cells is thought to enhance the collision rate between RBCs and the wall producing larger displacements and…”
Section: Discussionmentioning
confidence: 97%
“…λ > 3.2) was asserted as crucial for the formation of multi-lobed structures on the RBC membrane [62]. It is worth noting that previous simulations which reproduced the polylobe shape were either for simple shear flow [61,62,70] or planar Poiseuille flow [71] without the confinement of lateral walls.…”
Section: Simulated Rbc Morphology and Dynamicsmentioning
confidence: 91%
“…Whilst Pries et al originally postulated a recovery length of 10D (vessel diameter D ∈ [10,30] µm, in vivo measurements for rat mesenteric arterioles), Katanov et al [76] revealed via 3D simulations that a length up to 25D is needed for the CFL to fully develop in cylindrical microchannels (D ∈ [15,80] µm, haematocrit Ht ∈ [15%, 45%]). Also through simulations, Shaqfeh and co-workers [77,71] demonstrated moderately larger recovery lengths (beyond 36D h ) for the CFL to saturate in rectangular channels with comparable dimension and haematocrit levels (channel hydraulic diameter D h ∈ [20,30] µm, Ht ∈ [10%, 20%]). Under the circumstances of locally reduced flow or diluted RBC concentration in individual branches, the CFL recovery process may be further prolonged due to weakened hydrodynamic lift or lack of shear-induced diffusion.…”
Section: Cfl Development Between Arteriole-level Bifurcationsmentioning
confidence: 98%
“…It has been shown that significantly affects the RBC behavior in simple shear flow [ 7 , 8 , 9 , 10 ]. Only recently, several studies have confirmed that the viscosity contrast is important in microcapillary flow [ 6 , 11 , 12 , 13 , 14 ]. In [ 6 ], the authors study the dependence of the RBC shape and dynamics on the viscosity contrast in tube flow.…”
Section: Introductionmentioning
confidence: 99%